Common ragweed (Ambrosia artemisiifolia L.): allergenicity and molecular characterization of pollen after plant exposure to elevated NO2. (19th September 2015) - Zhao, Feng; Elkelish, Amr; Durner, Jörg; Lindermayr, Christian; Winkler, J. Barbro; Ruёff, Franziska; Behrendt, Heidrun; Traidl‐Hoffmann, Claudia; Holzinger, Andreas; Kofler, Werner; Braun, Paula; von Toerne, Christine; et al.
Abstract: Ragweed pollen is the main cause of allergenic diseases in Northern America, and the weed has become a spreading neophyte in Europe. Climate change and air pollution are speculated to affect the allergenic potential of pollen. The objective of this study was to investigate the effects of NO2, a major air pollutant, under controlled conditions, on the allergenicity of ragweed pollen. Ragweed was exposed to different levels of NO2 throughout the entire growing season, and its pollen further analysed. Spectroscopic analysis showed increased outer cell wall polymers and decreased amounts of pectin. Proteome studies using two‐dimensional difference gel electrophoresis and liquid chromatography–tandem mass spectrometry indicated increased amounts of several Amb a 1 isoforms and of another allergen with great homology to enolase Hev b 9 from rubber tree. Analysis of protein S‐nitrosylation identified nitrosylated proteins in pollen from both conditions, including Amb a 1 isoforms. However, elevated NO2 significantly enhanced the overall nitrosylation. Finally, we demonstrated increased overall pollen allergenicity by immunoblotting using ragweed antisera, showing a significantly higher allergenicity for Amb a 1. The data highlight a direct influence of elevated NO2 on the increased allergenicity of ragweed pollen and a direct correlation with an increased risk for human health. Abstract : Our study shows the influence of abiotic factors on the highly allergenic pollen from ragweed. Climate change and global warming as well as other environmental conditions have an influence on the plant and therefore might have also an influence on the allergenic potential of their pollen. We did proteomic studies and infrared spectroscopic analyses of pollen from the non‐model plant Ambrosia artemisiifolia to give more insight on how the pollen reacts to elevated NO2 . Allergenic proteins as well as allergen transcripts were increased under elevated NO2, and differences in cell wall components have been detected. Additionally, S‐nitrosylation of pollen proteins was shown and higher allergen recognition by immuno‐blot have been detected. Allergies are increasing, and the allergenic potential of the pollen is influenced by environmental factors. We used highly sophisticated methods, such as two‐dimensional difference gel electrophoresis analyses, and were able to detect, beside the well‐known Ambrosia allergens, a homolog to another plant allergen that reacted also with the sera of ragweed allergenic patients and therefore might modulate the Ambrosia allergenic response.